Gestión de prácticas de laboratorio y mantenimiento para el motor de un Mazda allegro 1600 c.c. de la Universidad Antonio Nariño sede Neiva. - Perdomo Rodríguez, Jonathan; Perdomo Canacué, Diego Oswaldo (Universidad Antonio Nariño, 2023)
The didactic bank of internal combustion existing in the Antonio Nariño University of the Neiva headquarters, is not currently working due to damage and lack of maintenance, this situation prevents students as teachers from performing laboratory practices in the subject of internal combustion engines. This project focuses on proposing the recovery of the 1600 c . c . Mazda Allegro engine. with which it will allow to carry out recognition and diagnosis of each of the parts for its operation to obtain an understand taken in (M . C . I). For the starting of the teaching up of the test bench, the characterization, analysis, as well as preventive and corrective maintenance were carried out, then the pre maintenance manuals were carried out. Finally, three poperational and ractical guides are delivered around the characterization of the engine, the temperature reading and the compression intake of cylinders to develop the concepts studied so that people from the Mechanical Engineering program obtain skills necessary for the Keywords: future as an engineer